Built with Alectryon, running Coq+SerAPI v8.13.0+0.13.0. Bubbles () indicate interactive fragments: hover for details, tap to reveal contents. Use Ctrl+↑Ctrl+↓ to navigate, Ctrl+🖱️ to focus. On Mac, use ⌘ instead of Ctrl.
Notation"[ rel _ _ | _ ]" was already used in scope
fun_scope. [notation-overridden,parsing]
Notation"[ rel _ _ : _ | _ ]" was already used in
scope fun_scope. [notation-overridden,parsing]
Notation"[ rel _ _ in _ & _ | _ ]" was already used
in scope fun_scope. [notation-overridden,parsing]
Notation"[ rel _ _ in _ & _ ]" was already used in
scope fun_scope. [notation-overridden,parsing]
Notation"[ rel _ _ in _ | _ ]" was already used in
scope fun_scope. [notation-overridden,parsing]
Notation"[ rel _ _ in _ ]" was already used in scope
fun_scope. [notation-overridden,parsing]
Notation"_ + _" was already used in scope nat_scope.
[notation-overridden,parsing]
Notation"_ - _" was already used in scope nat_scope.
[notation-overridden,parsing]
Notation"_ <= _" was already used in scope nat_scope.
[notation-overridden,parsing]
Notation"_ < _" was already used in scope nat_scope.
[notation-overridden,parsing]
Notation"_ >= _" was already used in scope nat_scope.
[notation-overridden,parsing]
Notation"_ > _" was already used in scope nat_scope.
[notation-overridden,parsing]
Notation"_ <= _ <= _" was already used in scope
nat_scope. [notation-overridden,parsing]
Notation"_ < _ <= _" was already used in scope
nat_scope. [notation-overridden,parsing]
Notation"_ <= _ < _" was already used in scope
nat_scope. [notation-overridden,parsing]
Notation"_ < _ < _" was already used in scope
nat_scope. [notation-overridden,parsing]
Notation"_ * _" was already used in scope nat_scope.
[notation-overridden,parsing]
Require Export prosa.util.nat prosa.util.rel prosa.util.list.(** In this section, we define and prove facts about superadditivity and superadditive functions. The definition of superadditivity presented here slightly differs from the standard one ([f a + f b <= f (a + b)] for any [a] and [b]), but it is proven to be equivalent to it. *)SectionSuperadditivity.(** First, we define subadditivity as a point-wise property; i.e., [f] is subadditive at [h] if standard subadditivity holds for any pair [(a,b)] that sums to [h]. *)Definitionsuperadditive_atfh :=
forallab,
a + b = h ->
f a + f b <= f h.(** Second, we define the concept of partial subadditivity until a certain horizon [h]. This definition is useful when dealing with finite sequences. *)Definitionsuperadditive_untilfh :=
forallx,
x < h ->
superadditive_at f x.(** Finally, give a definition of subadditive function: [f] is subadditive when it is subadditive at any point [h].*)Definitionsuperadditivef :=
forallh,
superadditive_at f h.(** In this section, we show that the proposed definition of subadditivity is equivalent to the standard one. *)SectionEquivalenceWithStandardDefinition.(** First, we give a standard definition of subadditivity. *)Definitionsuperadditive_standardf :=
forallab,
f a + f b <= f (a + b).(** Then, we prove that the two definitions are implied by each other. *)
forallf : nat -> nat,
superadditive f <-> superadditive_standard f
forallf : nat -> nat,
superadditive f <-> superadditive_standard f
f:nat -> nat
superadditive f -> superadditive_standard f
f:nat -> nat
superadditive_standard f -> superadditive f
f:nat -> nat
superadditive f -> superadditive_standard f
f:nat -> nat
superadditive_standard f -> superadditive f
f:nat -> nat
SUPER:superadditive f
a, b:nat
f a + f b <= f (a + b)
f:nat -> nat
superadditive_standard f -> superadditive f
f:nat -> nat
superadditive_standard f -> superadditive f
f:nat -> nat
superadditive_standard f -> superadditive f
f:nat -> nat
SUPER:superadditive_standard f
h, a, b:nat
AB:a + b = h
f a + f b <= f h
f:nat -> nat
SUPER:superadditive_standard f
h, a, b:nat
AB:a + b = h
f a + f b <= f (a + b)
byapply SUPER.Qed.EndEquivalenceWithStandardDefinition.(** In the following section, we prove some useful facts about superadditivity. *)SectionFacts.(** Consider a function [f]. *)Variablef : nat -> nat.(** First, we show that if [f] is superadditive in zero, then its value in zero must also be zero. *)
f:nat -> nat
superadditive_at f 0 -> f 0 = 0
f:nat -> nat
superadditive_at f 0 -> f 0 = 0
f:nat -> nat
SUPER:superadditive_at f 0
f 0 = 0
f:nat -> nat
SUPER:superadditive_at f 0
n:nat
Fx:f 0 = n.+1
n.+1 = 0
f:nat -> nat
SUPER:f 0 + f 0 <= f 0
n:nat
Fx:f 0 = n.+1
n.+1 = 0
f:nat -> nat
n:nat
Fx:f 0 = n.+1
~ f 0 + f 0 <= f 0
f:nat -> nat
n:nat
Fx:f 0 = n.+1
f 0 < f 0 + f 0
by ssrlia.Qed.(** In this section, we show some of the properties of superadditive functions. *)SectionSuperadditiveFunctions.(** Assume that [f] is superadditive. *)Hypothesish_superadditive : superadditive f.(** First, we show that [f] must also be monotone. *)
f:nat -> nat
h_superadditive:superadditive f
monotone f leq
f:nat -> nat
h_superadditive:superadditive f
monotone f leq
f:nat -> nat
h_superadditive:superadditive f
x, y:nat
LEQ:x <= y
f x <= f y
f:nat -> nat
h_superadditive:superadditive f
x, y:nat
LEQ:x <= y
f x <= f x + f (y - x)
f:nat -> nat
h_superadditive:superadditive f
x, y:nat
LEQ:x <= y
f x + f (y - x) <= f y
f:nat -> nat
h_superadditive:superadditive f
x, y:nat
LEQ:x <= y
f x <= f x + f (y - x)
f:nat -> nat
h_superadditive:superadditive f
x, y:nat
LEQ:x <= y
f x + f (y - x) <= f y
f:nat -> nat
h_superadditive:superadditive f
x, y:nat
LEQ:x <= y
f x + f (y - x) <= f y
f:nat -> nat
h_superadditive:superadditive f
x, y:nat
LEQ:x <= y
f x + f (y - x) <= f y
f:nat -> nat
h_superadditive:superadditive f
x, y:nat
LEQ:x <= y
x + (y - x) = y
by ssrlia.Qed.(** Next, we prove that moving any factor [m] outside of the arguments of [f] leads to a smaller or equal number. *)
f:nat -> nat
h_superadditive:superadditive f
forallnm : nat, m * f n <= f (m * n)
f:nat -> nat
h_superadditive:superadditive f
forallnm : nat, m * f n <= f (m * n)
f:nat -> nat
h_superadditive:superadditive f
n, m:nat
m * f n <= f (m * n)
f:nat -> nat
h_superadditive:superadditive f
n, m:nat
IHm:m * f n <= f (m * n)
m.+1 * f n <= f (m.+1 * n)
f:nat -> nat
h_superadditive:superadditive f
n, m:nat
IHm:m * f n <= f (m * n)
m * f n + f n <= f (m * n + n)
f:nat -> nat
h_superadditive:superadditive f
n, m:nat
IHm:m * f n <= f (m * n)
m * f n + f n <= f (m * n) + f n
f:nat -> nat
h_superadditive:superadditive f
n, m:nat
IHm:m * f n <= f (m * n)
f (m * n) + f n <= f (m * n + n)
f:nat -> nat
h_superadditive:superadditive f
n, m:nat
IHm:m * f n <= f (m * n)
m * f n + f n <= f (m * n) + f n
f:nat -> nat
h_superadditive:superadditive f
n, m:nat
IHm:m * f n <= f (m * n)
f (m * n) + f n <= f (m * n + n)
f:nat -> nat
h_superadditive:superadditive f
n, m:nat
IHm:m * f n <= f (m * n)
f (m * n) + f n <= f (m * n + n)
f:nat -> nat
h_superadditive:superadditive f
n, m:nat
IHm:m * f n <= f (m * n)
f (m * n) + f n <= f (m * n + n)
byapply h_superadditive.Qed.(** In the next section, we show that any superadditive function that is not the zero constant function (i.e., [f x = 0] for any [x]) is forced to grow beyond any finite limit. *)SectionNonZeroSuperadditiveFunctions.(** Assume that [f] is not the zero constant function ... *)Hypothesish_non_zero: existsn, f n > 0.(** ... then, [f] will eventually grow larger than any number. *)
f:nat -> nat
h_superadditive:superadditive f
h_non_zero:existsn : nat, 0 < f n
forallt : nat, existsn' : nat, t <= f n'
f:nat -> nat
h_superadditive:superadditive f
h_non_zero:existsn : nat, 0 < f n
forallt : nat, existsn' : nat, t <= f n'
f:nat -> nat
h_superadditive:superadditive f
h_non_zero:existsn : nat, 0 < f n
t:nat
existsn' : nat, t <= f n'
f:nat -> nat
h_superadditive:superadditive f
h_non_zero:existsn : nat, 0 < f n
t, n:nat
LT_n:0 < f n
existsn' : nat, t <= f n'
f:nat -> nat
h_superadditive:superadditive f
h_non_zero:existsn : nat, 0 < f n
t, n:nat
LT_n:0 < f n
t <= f (t * n)
f:nat -> nat
h_superadditive:superadditive f
h_non_zero:existsn : nat, 0 < f n
t, n:nat
LT_n:0 < f n
t <= t * f n
f:nat -> nat
h_superadditive:superadditive f
h_non_zero:existsn : nat, 0 < f n
t, n:nat
LT_n:0 < f n
t * f n <= f (t * n)
f:nat -> nat
h_superadditive:superadditive f
h_non_zero:existsn : nat, 0 < f n
t, n:nat
LT_n:0 < f n
t <= t * f n
f:nat -> nat
h_superadditive:superadditive f
h_non_zero:existsn : nat, 0 < f n
t, n:nat
LT_n:0 < f n
t * f n <= f (t * n)
f:nat -> nat
h_superadditive:superadditive f
h_non_zero:existsn : nat, 0 < f n
t, n:nat
LT_n:0 < f n
t * f n <= f (t * n)
f:nat -> nat
h_superadditive:superadditive f
h_non_zero:existsn : nat, 0 < f n
t, n:nat
LT_n:0 < f n
t * f n <= f (t * n)
byapply superadditive_leq_mul.Qed.EndNonZeroSuperadditiveFunctions.EndSuperadditiveFunctions.EndFacts.(** In this section, we present the define and prove facts about the minimal superadditive extension of superadditive functions. Given a prefix of a function, there are many ways to continue the function in order to maintain superadditivity. Among these possible extrapolations, there always exists a minimal one. *)SectionMinimalExtensionOfSuperadditiveFunctions.(** Consider a function [f]. *)Variablef : nat -> nat.(** First, we define what it means to find the minimal extension once a horizon is specified. *)SectionDefinitions.(** Consider a horizon [h].. *)Variableh : nat.(** Then, the minimal superadditive extension will be the maximum sum over the pairs that sum to [h]. Note that, in this formula, there are two important edge cases: both [h=0] and [h=1], the sequence of valid sums will be empty, so their maximum will be [0]. In both cases, the extrapolation is nonetheless correct. *)Definitionminimal_superadditive_extension :=
max0 [seq f a + f (h-a) | a <- index_iota 1 h].EndDefinitions.(** In the following section, we prove some facts about the minimal superadditive extension. Note that we currently do not prove that the implemented extension is minimal. However, we plan to add this fact in the future. The following discussion provides useful information on the subject, including its connection with Network Calculus: https://gitlab.mpi-sws.org/RT-PROOFS/rt-proofs/-/merge_requests/127#note_64177 *)SectionFacts.(** Consider a horizon [h] ... *)Variableh : nat.(** ... and assume that we know [f] to be superadditive until [h]. *)Hypothesish_superadditive_until : superadditive_until f h.(** Moreover, consider a second function, [f'], which is equivalent to [f] in all of its points except for [h], in which its value is exactly the superadditive extension of [f] in [h]. *)Variablef' : nat -> nat.Hypothesish_f'_min_extension : forallt,
f' t =
if t == h
then minimal_superadditive_extension h
else f t.(** First, we prove that [f'] is superadditive also in [h]. *)
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
superadditive_at f' h
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
superadditive_at f' h
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
a, b:nat
SUM:a + b = h
f' a + f' b <= f' h
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
a, b:nat
SUM:a + b = h
(if a == h
then minimal_superadditive_extension h
else f a) +
(if b == h
then minimal_superadditive_extension h
else f b) <=
(if h == h
then minimal_superadditive_extension h
else f h)
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
a, b:nat
SUM:a + b = h
(if a == a + b
then minimal_superadditive_extension (a + b)
else f a) +
(if b == a + b
then minimal_superadditive_extension (a + b)
else f b) <=
(if a + b == a + b
then minimal_superadditive_extension (a + b)
else f (a + b))
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
a, b, a':nat
EQa:a = a'.+1
b':nat
EQb:b = b'.+1
SUM:a'.+1 + b'.+1 = h
(if a == a + b
then minimal_superadditive_extension (a + b)
else f a) +
(if b == a + b
then minimal_superadditive_extension (a + b)
else f b) <= minimal_superadditive_extension (a + b)
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
a, b, a':nat
EQa:a = a'.+1
b':nat
EQb:b = b'.+1
SUM:a'.+1 + b'.+1 = h
f a +
(if b == a + b
then minimal_superadditive_extension (a + b)
else f b) <= minimal_superadditive_extension (a + b)
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
a, b, a':nat
EQa:a = a'.+1
b':nat
EQb:b = b'.+1
SUM:a'.+1 + b'.+1 = h
f a + f b <= minimal_superadditive_extension (a + b)
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
a, b, a':nat
EQa:a = a'.+1
b':nat
EQb:b = b'.+1
SUM:a'.+1 + b'.+1 = h
f a + f b <=
max0
[seq f a0 + f (a + b - a0)
| a0 <- index_iota 1 (a + b)]
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
a, b, a':nat
EQa:a = a'.+1
b':nat
EQb:b = b'.+1
SUM:a'.+1 + b'.+1 = h
f a + f b
\in [seq f a0 + f (a + b - a0)
| a0 <- index_iota 1 (a + b)]
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
a, b, a':nat
EQa:a = a'.+1
b':nat
EQb:b = b'.+1
SUM:a'.+1 + b'.+1 = h
a \in index_iota 1 (a + b)
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
a, b, a':nat
EQa:a = a'.+1
b':nat
EQb:b = b'.+1
SUM:a'.+1 + b'.+1 = h
f a + f b = f a + f (a + b - a)
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
a, b, a':nat
EQa:a = a'.+1
b':nat
EQb:b = b'.+1
SUM:a'.+1 + b'.+1 = h
a \in index_iota 1 (a + b)
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
a, b, a':nat
EQa:a = a'.+1
b':nat
EQb:b = b'.+1
SUM:a'.+1 + b'.+1 = h
f a + f b = f a + f (a + b - a)
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
a, b, a':nat
EQa:a = a'.+1
b':nat
EQb:b = b'.+1
SUM:a'.+1 + b'.+1 = h
f a + f b = f a + f (a + b - a)
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
a, b, a':nat
EQa:a = a'.+1
b':nat
EQb:b = b'.+1
SUM:a'.+1 + b'.+1 = h
f a + f b = f a + f (a + b - a)
byhave -> : a + b - a = b by ssrlia.}Qed.(** And finally, we prove that [f'] is superadditive until [h.+1]. *)
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
superadditive_until f' h.+1
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
superadditive_until f' h.+1
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
t:nat
LEQh:t < h.+1
a, b:nat
SUM:a + b = t
f' a + f' b <= f' t
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
t:nat
LEQh:t < h.+1
a, b:nat
SUM:a + b = t
LT:t < h
f' a + f' b <= f' t
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
t:nat
LEQh:t < h.+1
a, b:nat
SUM:a + b = t
GT:h < t
f' a + f' b <= f' t
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
t:nat
LEQh:t < h.+1
a, b:nat
SUM:a + b = t
EQ:t = h
f' a + f' b <= f' t
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
t:nat
LEQh:t < h.+1
a, b:nat
SUM:a + b = t
LT:t < h
f' a + f' b <= f' t
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
t:nat
LEQh:t < h.+1
a, b:nat
SUM:a + b = t
GT:h < t
f' a + f' b <= f' t
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
t:nat
LEQh:t < h.+1
a, b:nat
SUM:a + b = t
EQ:t = h
f' a + f' b <= f' t
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
t:nat
LEQh:t < h.+1
a, b:nat
SUM:a + b = t
LT:t < h
(if a == h
then minimal_superadditive_extension h
else f a) +
(if b == h
then minimal_superadditive_extension h
else f b) <=
(if t == h
then minimal_superadditive_extension h
else f t)
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
t:nat
LEQh:t < h.+1
a, b:nat
SUM:a + b = t
GT:h < t
f' a + f' b <= f' t
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
t:nat
LEQh:t < h.+1
a, b:nat
SUM:a + b = t
EQ:t = h
f' a + f' b <= f' t
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
t:nat
LEQh:t < h.+1
a, b:nat
SUM:a + b = t
LT:t < h
f a + f b <= f t
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
t:nat
LEQh:t < h.+1
a, b:nat
SUM:a + b = t
GT:h < t
f' a + f' b <= f' t
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
t:nat
LEQh:t < h.+1
a, b:nat
SUM:a + b = t
EQ:t = h
f' a + f' b <= f' t
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
t:nat
LEQh:t < h.+1
a, b:nat
SUM:a + b = t
GT:h < t
f' a + f' b <= f' t
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
t:nat
LEQh:t < h.+1
a, b:nat
SUM:a + b = t
EQ:t = h
f' a + f' b <= f' t
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
t:nat
LEQh:t < h.+1
a, b:nat
SUM:a + b = t
GT:h < t
f' a + f' b <= f' t
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
t:nat
LEQh:t < h.+1
a, b:nat
SUM:a + b = t
EQ:t = h
f' a + f' b <= f' t
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
t:nat
LEQh:t < h.+1
a, b:nat
SUM:a + b = t
EQ:t = h
f' a + f' b <= f' t
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)
t:nat
LEQh:t < h.+1
a, b:nat
SUM:a + b = t
EQ:t = h
f' a + f' b <= f' t
f:nat -> nat
h:nat
h_superadditive_until:superadditive_until f h
f':nat -> nat
h_f'_min_extension:forallt : nat,
f' t =
(if t == h
then
minimal_superadditive_extension
h
else f t)